2004
DOI: 10.1108/13639510410553095
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of officer peer retaliation

Abstract: A survey of the literature shows that researchers have assessed the social processes of retaliation among adversarial crime prone populations. However, notably absent from this research is the study of peer retaliation among non‐adversarial and less crime prone populations, such as police officers. The underlying theoretical premise is that peer retaliation, defined here as a mechanism of social control, operates under prevailing police culture conditions.Using focus group interviews collected from one large S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Occupational stress may occur to police officer who perceives themselves as having a strong peer relation. Cancino and Enriquez (2004) noted that peer influence is an exceptionally important social force. Shared work experiences allow officers to develop mutual understanding of work stressors that can serve as a protective factor.…”
Section: Interpersonal Relationships In the Police Servicementioning
confidence: 99%
“…Occupational stress may occur to police officer who perceives themselves as having a strong peer relation. Cancino and Enriquez (2004) noted that peer influence is an exceptionally important social force. Shared work experiences allow officers to develop mutual understanding of work stressors that can serve as a protective factor.…”
Section: Interpersonal Relationships In the Police Servicementioning
confidence: 99%
“…Peer bonds within policing can lead to intense secrecy and solidarity among officers, limiting their willingness to disclose observed gendered (and other) behavior. In fact, officers who report problems presented by their peers might fear retaliation from others within the department (Cancino and Enriquez 2004). The lead author, who has considerable experience working with police officers in a professional setting, conducted the interviews and took measures to build rapport.…”
Section: Interviews Coding and Limitationsmentioning
confidence: 99%
“…The informal police culture remains a powerful roadblock to major behavioral change (Cancino and Enriquez 2004). The normative standard in policing pushes officers toward risk-seeking behavior.…”
Section: Reinventing the Matron 257mentioning
confidence: 99%
“…A New Zealand study by Frewin and Tuffin (1998, p.181) of homosexuality in policing identified what they called 'internal pressure discourse' with resources of marginalisation, isolation, surveillance of peers by peers, rumours, and threats to safety which are performed 'on those who fail to conform': who fail to function as committed team members. Studies by Frewin and Tuffin (1998) and Cancino and Enriquez (2004) found that police culture and peer retaliation function as forms of social control to essentially maintain the status quo.…”
Section: Defining the D/discoursesmentioning
confidence: 99%